Research of intensity of tires wear of trucks in the process of their operation - Sakno, O. P.; Сакно, О. П. (Харківський національний автомобільно-дорожній університет, 2013)
The dependences intensity of tires wear on the tire life of trucks are determined on the basis of the system measurements of residual tread depth in the actual operating conditions. The factors which influence the critical rate of tire wear are analyzed.
Исследование интенсивности износа шин грузовых автомобилей в процессе их эксплуатации
Дослідження інтенсивності зносу шин вантажних автомобілів в процесі їх експлуатації
Keywords: tire; truck; tire wear; tire life; tread depth; шина; грузовой автомобиль; износ; ресурс шин; высота рисунка протектора; вантажний автомобіль; знос; висота рисунка протектора; 629.017:629.083